ANALISIS PERILAKU NIAT BERPINDAH PENGGUNA JASA LAYANAN RUMAH KOS (Studi pada konsumen rumah kos di Sampangan) - Dian Ika Saputri, 15.05.51.0034; Marlien, RA (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of service quality, price, location, and facilities on the intention to move users of boarding house services in Sampangan. The population in this study are consumers who use boarding house services in Sampangan, because the population is very large, this study took a sample of 106 respondents. The sampling technique in this study used purposive sampling, namely the technique of determining samples with certain criteria, namely people who use the services of a boarding house in SampanganThe data used in this study is primary data, with a questionnaire as a research instrument. The analytical tool used is multiple linear regression, validity test, reliability test, F test, coefficient of determination test (R²), and t test, which is then processed by calculation of SPSS (Statistical Product and Solutions) version 19.The results showed that service quality has a positive and significant effect on intention to move, price has a positive and significant effect on intention to move, location has a positive and not significant effect on intention to move and facilities have a positive and insignificant effect on intention to move